Post Tonsillectomy Pain Relief: Comparative Study between Peritonsillar Infiltration of Bupivicain and Intramuscular Diclofenac (Tikrit Journal of Pharmaceutical Sciences, 2023)
Hospital based study carried out on (40) patients from both sexes, aged (4-26) years,underwent Tonsillectomy by dissection method during the period extend from (June2012 to September 2012). The Patients were divided into two groups- Group A (18)patients: include those with pre-incisional – infiltration of bupivicain with subsequent(spray) post operatively on Tonsils bed at evening and next morning. Group B (22)patients: include those patients with diclofenac intramuscular injection, half hourbefore operation with subsequent doses at evening and next morning. (Result): nodifference in history of post- operative nausea and vomiting regarding the two groups.The mean operative time for group (A) was (28.9) minutes, while the mean operativetime for group (B) was (29.5) minutes. Both groups showed no difference regardingreactionary bleeding (bleeding occurs within 24 hours) or secondary bleeding(Bleeding occurs after 6-8 days due to infection). Group (A) showed low score of painin immediate post-operative time but it was not significant, while group (B) showedlow score of pain in most of the cases at evening, it was significant. No difference inboth groups in the next morning both showed low score of pain. Conclusion:intramuscular diclofenac is more potent as pain relief if compare with Bupivicaininfiltration. Aim of study: To identify the effect of infiltration of bupivicain for posttonsillectomy pain-relief and in compare to intramuscular injection of diclofenac.